"Hep C, where art thou": What are the remaining (fundable) questions in hepatitis C virus research?. Issue 1 (15th November 2016) - Rosen, Hugo Ramón
Abstract : Hepatitis C virus (HCV) has dominated the field of hepatology for the past 25 years, and its cure in the majority of treated patients is one of the greatest achievements in all of medicine. However, the latter has led to the belief by some that HCV research should be shelved for other, more pressing areas. The mission for HCV eradication is far from accomplished. As a historical reference, we should consider that disease elimination has required vaccination with all previously controlled infections including smallpox and polio and that simple, effective treatment is not sufficient in most infections to lead to substantial control. Syphilis is the best example, for which a single dose of penicillin (which literally costs pennies and that we have had since 1945) is curative in early stages. Not only have we not eradicated syphilis, rates of infection have increased in many places within the United States in recent years. Most HCV‐infected subjects are unaware of their infection, remaining at risk for transmission to others and disease progression, including cirrhosis and hepatocellular carcinoma. In the era of highly effective direct‐acting antivirals (DAAs), many questions pertaining to HCV remain, but they are more complex and difficult to answer. Here, I provide my perspective on some of these salient issues: the residual risk for disease progression after sustained virologic response, the optimal approach to current DAA failures, the impact of targeting people who inject drugs with DAAs, vaccine prospects, and application of neutralizing HCV glycoprotein antibodies. (Hepatology 2017;65:341‐349).